Evaluation of corn particle size on the growth performance, intestinal permeability, pellet quality, and litter moisture of turkey hens raised without antibiotics - A.M. Lyons; J.S. Moritz; J.W. Boney; M.E. Persia (Journal of Applied Poultry Research, 2024)
SUMMARY: An experiment was conducted to determine the effects of corn particle size (CPS) on turkey hen poult performance, intestinal permeability (IP), and litter dry matter. A total of 1,584 Hybrid turkey hen poults were raised in floor pens from 0 to 42 d. Poults were fed a crumbled starter 1 and pelleted starter 2 diet. The experiment was a 2 × 2 factorial with CPS in diet phase starter 1 (fine and coarse) and CPS in diet phase starter 2 (fine or coarse), resulting in 4 treatments of 18 replicates of 22 turkeys. Corn was ground using a hammermill with a 4.76 mm screen (581 µm; fine) or a 6.35 mm screen (964 µm; coarse). Pellet quality was determined using pellet durability index (PDI), modified pellet durability index (MPDI), and New Holmen Pellet Tester (NHPT). Body weight and feed intake were measured on D0 and D42. Feed conversion ratio was calculated from 0 to 42 d. Litter dry matter content and IP were measured on D42. Data were analyzed using JMP Pro 16.0 (P ≤ 0.05) and means were separated using Student's t test. Corn particle size did not impact starter 2 pellet quality (PDI, MPDI, and NHPT; P > 0.05). There were no interactions between dietary phase and CPS over 0 to 42 d. Overall, there was a CPS main effect over the starter 1 phase and hens fed coarse corn had decreased FI (P ≤ 0.01) and BW (P ≤ 0.01), however FCR was not affected (P > 0.05). Day 42 IP and litter dry matter content were not influenced by CPS in either diet phase (P > 0.05). These data indicate that coarse corn decreases both FI and BW of turkey hens when fed during starter 1, but had no effects on FCR, IP, and litter dry matter content when fed in starter 2. Although fine ground corn was needed to maximize performance in the starter 1 phase, coarse ground corn may be able to maintain turkey hen performance in the starter 2 phase while reducing milling costs.